A Case Report of Methylobacterium radiotolerans Bacteremia and Brain Abscesses. Issue 2 (28th June 2021) - Tang, Wesley; Desai, Alpa; Desai, Kunal
Abstract : Abstract: Methylobacterium radiotolerans is a ubiquitous organism found in the environment and is considered an opportunistic pathogen of low virulence in humans. Most human infections from M. radiotolerans have been reported in immunocompromised hosts and have been reported mainly as bloodstream infections related to central venous catheters. We present the first known case of M. radiotolerans as a causative agent of multiple brain abscesses in an immunocompromised host.